Stunting Paradigm by Adolescent Cadres: A Qualitative Study in the Urban Area of Yogyakarta City - Afroh Fauziah; Giyawati Yulilania Okinarum; Metty Metty (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2025)
The stunting condition is triggered by malnutrition, from the womb until the child (especially women) enters adolescence, namely the first 8000 days of life (HPK). Fulfilment of proper nutritional needs must be provided since that time. Therefore, the author has designed a grand design for the formation of adolescent cadres for stunting prevention in urban areas of Yogyakarta City since 2022. This study aims to further analyse how the paradigm of stunting by adolescent cadres. This research uses qualitative methods, with a descriptive qualitative design, conducted for 3 months, in 2023, in Tegalrejo District, Yogyakarta City. Total sampling was the sampling technique in this study, involving 10 adolescent cadres as participants. Data were collected through in-depth interviews of approximately 45 minutes, with each participant. Data were analysed using six stages of thematic analysis, including: data introduction; initial coding; theme search; theme study; theme definition and naming, and reporting. NVivo 12 software was used by the researcher to conduct iterative data management and emerging themes. The findings showed three themes on the stunting paradigm by adolescents: the urgency of eliminating stunting stigmatisation, the fundamentalism of parental readiness in childcare, and the importance of adolescent cadres moving in each school. Adolescent cadres have understood the current stunting paradigm, that its reduction is urgent to create healthy generations in the future.